Analisis Tingkat Kriminalitas Di Propinsi Dengan Pendekatan Data Panel - Murialti, Neng; Hadi, Muhammad Fikry (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This study aims to find out how the influence of population density, education, poverty, unemployment, wage and migration rates on the level of crime in 6 regencies /cities in Riau Province in 2017-2021. The results of this study show that three variables of population density, unemployment and poverty have no significant effect on the level of criminality while the educational, positive and significant variables affect the level of crime, while the wage level has a negative and significant effect on crime rates and for migration variables enter positive and significant effects on Criminal level in 6 districts/cities in Riau Province in 2017-2021.